Hematohidrosis - A rare entity. - Jayakar, T.; Soundarya, S. (European Journal of Pediatric Dermatology, 2024)
Hematohidrosis is a rare disease characterized by blood exudation from the intact skin or mucosa. It occurs mostly in healthy adolescents as an unusual reaction to anxiety. It has a benign course but must be known to avoid unnecessary family concerns and laboratory tests. A case was reported in a 14-year-old boy, its differential diagnosis was discussed and a diagnostic algorithm was proposed.